RECURSO EDUCATIVO EN LÍNEA SOBRE TIPOGRAFÍA: Aprende tipografía de buena fuente - ACOSTA, MONICA (Revista Ecos de la Academia, 2021)
University education has a new challenge: to solve the demands of a society that lives with technology. The teaching - learning processes require an update according to the new educational contexts and environments, with the priority being the curricular needs of the students. The university classroom has technological equipment, the Ecuadorian university has teachers trained with a fourth professional level, students are related to information and communication technologies; The question raised is that if these components are being combined in favor of graphic education, such as the teaching of Typography. This research focuses on autonomous learning strategies in graphic design students of the Universidad Técnica del Norte - Ecuador, using information and communication technologies. The proposal of a Massive Open Online Course of typography in three stages is developed: design, implementation and validation. The course is developed in the Google - Course builder tool, the free access online implementation and validation is contacted by university design professors in Nicaragua, Indonesia and Turkey, as evaluators.